Virtual Reality Based Hypermedia Training for Teachers of MAN 2 Model Makassar - Hambali, Uyunnasirah; Natsir, Ratu Yulianti; Nasir, Nasir (Pustaka Digital Indonesia, 2023)
This Community Service Activity (PKM) aims to; (1) provide an introduction to teachers at MAN 2 Model Makassar regarding Virtual Reality learning media as an alternative IT-based learning media, and (2) train MAN 2 Model Makassar teachers to be able to utilize Virtual Reality-based learning media. The methods applied in this service program are the presentation method, the demonstration method, and the practical method. The presentation method is applied in the introduction of hypermedia software using the millers lab application, its benefits, and its application in making virtual reality-based media, demonstration methods regarding program operations and practical methods where teachers practice directly making learning media according to their respective subjects with the use of media-based virtual reality